Effective silicon nanowire arrays/WO3 core/shell photoelectrode for neutral pH water splitting. (13th June 2017) - Chen, Zhen; Ning, Minghui; Ma, Ge; Meng, Qingguo; Zhang, Yongguang; Gao, Jinwei; Jin, Mingliang; Chen, Zhihong; Yuan, Mingzhe; Wang, Xin; Liu, Jun-Ming; Zhou, Guofu
Abstract: We report the first demonstration of a high-efficiency photoelectrochemical (PEC) water splitting reaction using a novel Si NWs/WO3 core/shell photoanode prepared by a mild and inexpensive metal-catalyzed electroless etching process followed by dip-coating, airing and annealing methods. The dense and vertically aligned Si NWs/WO3 core/shell nanostructure were characterized by scanning electron microscopy, transmission electron microscopy and x-ray diffraction. In comparison to planar n-Si, Si NWs and planar Si/WO3, the Si NWs/WO3 samples showed significantly enhanced photocurrent over the entire potential sweep range. More significantly, the Si NWs/WO3 samples have an exceptionally low photocurrent onset potential of −0.6393 V versus reversible hydrogen electrode (RHE), indicating very efficient charge separation and charge transportation processes. The as-prepared electrode also has a photocurrent density of 2.7 mA cm −2 at 0.6107 V versus RHE in 0.5 M Na2 SO4 solution under simulated solar light irradiation (100 mW cm −2 from 300 W Xenon lamp coupled with an AM 1.5 G filter). An optimal solar-to-hydrogen efficiency of about 1.9% was achieved at 0.2676 V versus RHE. Electrochemical impedance spectroscopy was conducted to investigate the properties of the charge transfer process, and the results indicated that the enhanced PEC performance may due to the increased charge separation. The x-ray photoelectron spectroscopy measurements indicated the chemical composition of the Si NWs/WO3 nanostructure. Our work has provided an efficient strategy to improve the energy conversion efficiency and photocurrent of water splitting materials.